When worlds collide: Challenges to implementing communication research in community oncology practices. Issue 5 (May 2020) - Brannen, Elise N.; Pollak, Kathryn I.; Farrell, David; Baranowski, Rebecca A.; Arnold, Gerald K.; Rohowyj, Nancy; Goldman, Julie L.; Tulsky, James A.
Highlights: Implemented an online communication training intervention in community practices. Significant barriers to research in community practices: time, burden, support. To best integrate research into practice, researchers must work with oncologists. Support, limiting burden, increasing flexibility, and thorough pilot testing are key. Abstract: Objective: During a recent trial assessing the effectiveness of an online communication training for community practice oncologists, we encountered multiple barriers. Methods: We asked oncologists to participate through the American Board of Internal Medicine (ABIM) Maintenance of Certification program. Oncologists collected 25 Clinician and Group Consumer Assessment of Healthcare Providers (CAHPS) surveys from patients and 4 audio-recorded clinic encounters. They then completed either the ABIM Action Plan (control) or the online Study of Communication in Oncologist Patient Encounters (SCOPE) program (intervention). Oncologists collected another 25 CAHPS surveys and 4 audio-recorded encounters as follow-up. Results: We enrolled 146 oncologists in the study. Only 27 completed the study; another 27 actively withdrew, and 94 did not complete the study. We identified four main challenges to participation: commitment discrepancies, burden of research, informed consent, and technology. We introduced efforts to overcome these barriers with success limited by time and resources. Conclusion: When conducting research in community practices, investigators must provide significant support, limit burden, increase flexibility, and conduct thorough pilot testing. Practice implications: To improve patient care, research must translate well into the workflow of actual practices. Assessing our experience, we identified challenges and effective solutions to be used by investigators as they plan and implement future communication interventions.